PROBLEMS FACED BY FISHERMEN IN DISTRIBUTING FISH CATCHES IN BATANG REGENCY - Salam, Galih Abdu; Arsal, Thriwaty (Program Studi Sosiologi Universitas Malikussaleh, 2024)
Indonesia as a maritime country with great marine potential should be able to provide welfare for the fishing community. However, in reality, most fishermen in Indonesia, including in Mangunsari Village, still live in poverty. This research aims to identify and analyze the problematic distribution of fish catches in Mangunsari Village. The research questions focused on infrastructure, technology, and market access constraints faced by fishermen. This research uses qualitative methods with in-depth interviews and participatory observation to explore the problems faced by fishermen. The research findings show that poor infrastructure, limited storage and preservation technology, and limited market access are the main obstacles in fish distribution. In addition, the influx of investors building the Batang Integrated Industrial Estate (KITB) and the construction of a toll road that led to flash floods also worsened the situation, forcing fishermen into debt to make ends meet. Ineffective government policies and low community participation in utilizing aid also exacerbated the condition. The findings are expected to serve as a basis for formulating more effective strategies to improve the welfare of fishing communities in Mangunsari Village.